Richard J. A. Talbert, Rome's world. The Peutinger Map Reconsidered - Turković, Tin (Array, 2011)
Article is a review of the recently published book in which R. J. A. Talbert offered his interpretation of the so-called Peutinger's map (Vodex Vindobonensis 324). Considering that the book is the first attempt, after a long period of 60 years, to reexamine the map, its making and its medievale fate, the intention built into the review was to as closely as possible examine arguments and hypotheses presented by Talbert.